The forgetting of Hegel in Ernesto Laclau: An unfortunate disengagement - Retamozo Martin (Filozofija i Društvo)
Ernesto Laclau criticises Hegelian dialectics for allegedly introducing the logic of necessity into Marxism, which, he argues, hinders the consideration of contingency. This article examines Laclau’s interpretation of Hegelian dialectics across various works and scrutinises his exploration of the concepts of determination, negativity, and contingency. Revisiting these concepts may offer a non-deterministic understanding of dialectics more aligned with post-foundational political thought, thereby facilitating reflection on social ontology and antagonisms.